Unequal effects of the economic cycle on human capital investment. Evidence from Italian panel data - Luca Bonacini (Global Labor Organization (GLO), 2020)
Human Capital Theory considers individuals' education as an investment in terms of money, time, effort, and the renouncement of income opportunities that they expect will be compensated during their working life. While these benefits are mainly in the long run, direct and indirect costs are conditioned by the present circumstances, and in particular, by the macroeconomic conditions. The literature investigating the influence of the business cycle on enrolment decisions often suggests a counter-cyclical relationship without considering that economic fluctuations can produce heterogeneous effects among households facing different economic situations. Through a fixed effects regression based on panel data from the Italian component of the EU-SILC survey, I find the existence of a counter-cyclical propensity to enrol that is symmetric to the stages of the economic cycle. However, after disaggregating the analysis by household income quartiles, results show that a 1% increase in GDP reduces the probability of the poorest individuals being enrolled in non-compulsory education by 1.2%, while the wealthier portion of the population shows an a-cyclical relationship. The policy implications of these results are particularly important as they suggest that measures directed towards youths from poorer households to promote their enrolment in non-compulsory education should be strengthened when economic conditions improve.
Keywords: A22; E32; I23; I24; 330; Economic cycle; Educational economics; Human capital; Rate of return